Subjectively and objectively assessed social and physical environmental correlates of preschoolers' accelerometer-based physical activity - Michael Eichinger; Sven Schneider; Freia De Bock (BMC, 2017)
Abstract Background Overweight and low levels of physical activity (PA) in preschoolers are major public health concerns. However, to date only few studies have investigated subjective and objective correlates of PA across different socioecological domains in preschoolers. We therefore simultaneously investigate associations between preschoolers' objectively measured leisure-time PA and a comprehensive set of subjective and objective potential PA correlates across the behavioral, social and physical environmental domains on both family- and community-level. Methods In this cross-sectional study time spent in moderate-to-vigorous PA (MVPA) and total PA (TPA) were measured by combined accelerometry and heart rate monitoring in 735 3-6 year-old children from 52 preschools in Southern Germany. Family- and community-level potential correlates of PA from different domains (behavioral, social and physical environmental) were subjectively (i.e. by parent proxy-report) and objectively assessed. Their associations with PA on weekend days and weekday afternoons were tested by covariate-adjusted multilevel regression models. Results While none of the objective social and physical environmental factors showed associations with PA, subjective parental traffic safety perceptions were positively associated with MVPA and TPA on weekends. Also, preschoolers' participation in organized sports was positively correlated with MVPA (on weekends) and TPA (both on weekends and weekday afternoons). Conclusion Subjective traffic safety perceptions and participation in organized sports, an indicator and a result of parental support towards PA - i.e. subjective parental perceptions of environmental factors and family-level correlates which are more proximal to preschoolers - might be more central to PA in preschool age than objectively assessed community-level environmental features which tend to be more distal correlates. If replicable, targeting parental perceptions of environmental factors and parental support for PA in preschool age might be powerful leverages for public health policy.